Contributors to caregiver burden, depression, and anxiety in the partners of professional American-style football players: a cross-sectional study - Konstantinides, Niki; Atkeson, Paula S.; DiGregorio, Heather; Dairi, Inana; Brown, Cheyenne; Noriega, Kairi; Baker, Jillian; Taylor, Valencia; Glass, Christy; Kazis, Lewis E.; Terrill, Rachel; Speizer, Frank E.; et al. (Frontiers in Psychology, 2025)
IntroductionAmerican-style football (ASF) has been linked to chronic adverse health outcomes. The extent to which ASF players' careers impact their spouses' caregiver burden, depression, and anxiety remains unknown. In addition to conventional family stressors, ASF families may have specific concerns such as chronic traumatic encephalopathy (CTE; a condition that can only be established at autopsy), which may additionally contribute to caregiver burden and mood symptoms.MethodsFamily Experiences Managing Football Lives (FEM-FL) is a cross-sectional study developed under the Football Players Health Study at Harvard University. Eligible participants were partners of current and former professional ASF players who completed electronic surveys from 2021 to 2024. Data on age, race, family composition, income, employment status, caregiver help, personal health, marital satisfaction, player position, and number of relocations were collected. Participants were asked whether they believed their partner had “CTE.” Multivariable models measured associations between established and ASF-specific risk factors and caregiver burden (Zarit 4-item Burden Interview), and depression and anxiety symptoms (Patient Health Questionnaire-4).ResultsAmong 153 partners of active and former professional ASF players, mean [SD] age was 48.1 [13.5], and 28.8% self-identified as Black. In models that adjusted for established risk factors and ASF-specific variables, poor health among partners was associated with a 1.6 point increase in depression score (95% CI = 0.90, 2.30; p < 0.001) and 1.87 point increase in anxiety (95% CI = 1.05, 2.69; p < 0.001). Models that controlled for established risk factors identified significant associations between increased marital satisfaction and a 5.87 reduction in caregiver burden score (95% CI= −7.32, −4.43; p < 0.001), 1.26 score reduction in depression score (95% CI = −1.75, −0.77; p < 0.001) and 1.32 reduction in anxiety score (95% CI = −1.89, −0.75; p < 0.001). CTE concerns were associated with a 2.90 increase in caregiver burden score (95% CI = 1.78, 3.99; p < 0.001) and a 0.44 increase in reported anxiety (95% CI = −0.01, 0.88; p = 0.05), but had no association with depression in adjusted models.DiscussionAmong partners of active and former professional ASF players, marital satisfaction, poor health, and concerns about CTE may play a role in caregiver burden and behavioral health. CTE concerns represents a potential novel risk factor for increased caregiver burden among partners of ASF players.